Afterlives of Affect : Science, Religion, and an Edgewalker's Spirit - Watson, Matthew C., 1981- (Book collections on Project MUSE., 2020)
"In AFTERLIVES OF AFFECT, Watson considers the life and work of Mayanist Linda Schele (1942 - 1988) as an entry point to discuss the nature of cultural inquiry and the metaphor of decipherment in anthropology. Watson figures Schele as a trickster guide in his experimental, person-centered ethnography, reanimating the work of decipherment and drawing upon an "affect of discovery" that better expresses the affective engagement of anthropologists and their subject of study. Through her archive, Watson finds an archaeologist wholly animated by her fieldsite and immersed in a more "spiritual science," though nonetheless still imbricated in a system of settler-colonial knowledge production. By holding Schele's work in conversation with both her own interlocutors and prominent voices in the field today, Watson refocuses on anthropologists who are engaged as individuals; carrying their own attachments with them as they describe, interpret, and decipher what they observe, and in doing so, positions affective engagement as a constitutive element in a more reflexive anthropology. The book is organized into six chapters that progress thematically through Schele's life and Watson's autoethnographic reflections on his own research. In Sacrilege (chapter 1), Watson draws together moments throughout his research where he felt his exhumation of Schele's work veered too closely to disturbing what was laid to rest-much like Schele's own work, which relied on the unearthing of sites long laid to rest, reanimating long-dead Mayan rulers and artists. The chapter sets the tone of the work as always toeing the line and risking the introduction of the mystical and affective into scientific interpretation-edgewalking with Schele. In Animals (chapter 2), Watson draws upon metaphors in the animal world, as did Schele when she sought inspiration for her next moment of insight; spider webs present a Geertzian metaphor for webs of signification, while rabbits are trickster guides, a transtemporalizing technology, drawing Schele (and Watson) forward and back through time. Through these reflections, Watson builds iteratively on arguments throughout the book that return to themes more recognizable in contemporary theory conversations: more-than-human worlds, the question of modernity, and the social conditions of knowledge production. This book will be of interest to readers in anthropology, especially those engaged in the ontological turn and more-than-human worlds, as well as the history of anthropology and anthropology theory more broadly. This book will also be of interest to readers in science studies, the posthumanities, and affect theory"--